Immunogenicity of the 9-Valent HPV Vaccine Using 2-Dose Regimens in Girls and Boys vs a 3-Dose Regimen in Women. Issue 7 (July 2017) - Iversen, Ole-Erik; Miranda, Maria Jose; Ulied, Angels; Soerdal, Terje; Lazarus, Erica; Chokephaibulkit, Kulkanya; Block, Stan L.; Skrivanek, Ales; Nur Azurah, Abdul Ghani; Fong, Siew Moy; Dvorak, Vladimir; Kim, Kyung-Hyo; et al.
Abstract : (Abstracted from JAMA 2016;316:2411–2421) Diseases caused by human papillomavirus (HPV) infections are a substantial health care burden in both the developing and developed world.